Inflammatory Myofibroblastic Tumor Arising in the External Ear: Unexpected Location (Case Report and Review of Literature) - Al-Humidi, Ahmed; Al-Khamiss, Abdullah (International Journal of Health Sciences, 2015)
We present an unexpected extremely rare case of an inflammatory myofibroblastic tumor (IMT) of the external ear. A 3-year-old boy presented with a mass arising on the posterior aspect of the left ear lobule and extending to the external auditory canal. This mass grew slowly and showed no skin changes. Radiologically, it was diagnosed as a vascular tumor. Surgical excision and primary closure was performed for the patient. Histopathologic examination demonstrated a circumscribed noncapsulated mass formed by a proliferation of spindle cells in deep dermis and subcutaneous tissue. The spindle cells were mixedwith lymphoplasmacytic infiltration compatible with the IMT. Because it is very rare to arise in this location, we present this case as a case report with details histopathological examinationand reviewed the English literature for similar cases. Â  Â 